Evaluation of wind energy potential and electricity generation at six locations in Turkey - Ucar, Aynur; Balo, Figen (Elsevier Sci Ltd, 2009)
In this study, wind characteristics were analyzed using the wind speed data collected of the six meteorological stations in Turkey during the period 2000-2006. The annual mean wind speed of the six stations (Erzurum, Elazig, Bingol, Kars, Manisa and Nigde) is obtained as 8.7, 8.5, 5.9, 6.9, 7.4 and 8.0 m/s at 10 m height, respectively. The mean annual value of Weibull shape parameter k is between 1.71 and 1.96 while the annual value of scale parameter c is between 6.81 and 9.71 m/s. A technical assessment has been made of electricity generation from four wind turbines having capacity of (600 kW, 1000 kW, 1500 kW and 2000 kW). The yearly energy output and capacity factor for the four different turbines were calculated. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; Weibull distribution; Wind turbine